Validity of the Simplified Computerized Comprehensive Learning Ability Screening Test for the Early Detection of Learning Disabilities - Eun Kyoung Lee; Hannah Huh; Woo Young Kim; Hyunju Lee; Hanik Yoo (Psychiatry International, 2025)
This study aimed to validate the usefulness of the Simplified Computerized Comprehensive Learning Ability Screening Test (SCLST) in schools and homes, to facilitate early detection and intervention for children with reading disorder (RD), math disorder (MD), or attention-deficit hyperactivity disorder (ADHD). Participants included 207 children and adolescents diagnosed with ADHD, RD, or MD and the healthy control group that was matched 1:1 by gender, age, and educational years. Higher rates of omission errors, commission errors, and standard deviation of response times were observed in the ADHD group (p < 0.001) in the SCLST-ADHD. The accuracy rates of the SCLST-RD and SCLST-MD were lower in the RD (p < 0.001) and MD group (p < 0.01), respectively. The mean response times were higher in the MD group (p < 0.001). In addition, the optimal sensitivity and specificity values were 84.6% and 88.5%, and the positive and negative predictive values were 88.0% and 85.2%, respectively, in the SCLST-ADHD. In the SCLTS-RD, the sensitivity and specificity values were 81.1% and 85.6%, and the positive and negative predictive values were 84.9% and 81.9%, respectively. In the SCLST-MD, the sensitivity and specificity values were 97.4% and 76.9%, and the positive and negative predictive values were 80.9% and 96.8%, respectively. Thus, by supporting timely assessment and intervention, this tool can support clinicians and educators in early-stage learning disabilities screening and reduce long-term psychosocial impairments.